2018
DOI: 10.1093/milmed/usx199
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of QuickDASH Scores for Three Hand Therapy Acute Upper Limb Conditions

Abstract: The results did not support the QuickDASH 80% cut point test as a predictor of final outcome in these three patient populations. Patients with the worse initial 20% scores were not correctly classified as worse 20% final scores. This study provides summary data from three upper limb conditions to provide clinicians with comparison data to establish goals and educate patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, PRC 1 RCPI demonstrated more favorable Quick-DASH and PRWHE scores than PRC (17 vs. 26 and 14 vs. 22, respectively), as well as preoperative to postoperative improvement in the PRWHE score (251 vs. 238). Again, this must be investigated for clinically meaningful differences; prior reports for MCID of PRWHE range from 7.7 to 14 [20][21][22] and 14 to 19 for QuickDASH 23,24 . Thus, PRC and PRC 1 RCPI both appear to provide meaningful clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, PRC 1 RCPI demonstrated more favorable Quick-DASH and PRWHE scores than PRC (17 vs. 26 and 14 vs. 22, respectively), as well as preoperative to postoperative improvement in the PRWHE score (251 vs. 238). Again, this must be investigated for clinically meaningful differences; prior reports for MCID of PRWHE range from 7.7 to 14 [20][21][22] and 14 to 19 for QuickDASH 23,24 . Thus, PRC and PRC 1 RCPI both appear to provide meaningful clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Outcome assessments included the quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire, pain Visual Analog Scale (VAS) and function VAS. The 11‐item QuickDASH as a shortened version of 30‐item DASH was used as the primary outcome measure in order to evaluate the patients physical function and symptoms [6, 24]. VAS for pain and VAS for function, those were collected pre‐ and post‐operatively as routinely were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we excluded mild patients to clarify the characteristics of wrist torque in patients with LE. As previous studies reported quick disabilities of the arm, shoulder, and hand (QuickDASH) scores of 11-15 points at the end of conservative treatment for LE, 19,20 we set a cutoff score of QuickDASH for exclusion criteria of patients with mild LE as 11.…”
Section: Participantsmentioning
confidence: 99%